MOTIF SOPIR MEMODIFIKASI ANGKOT (STUDI KASUS SOPIR ANGKOT TRAYEK SITEBA-PASAR RAYA PADANG) - -, JEFRINALDI - (Pendidikan Sosiologi, 2014)
This research was motivated by a discrepancy between the public transportation in thecity of Padang with Law No. 22 of 2009 on road transport, which is stated in article 148, article 52and article 48 paragraph 2. Most public transportation in the city of Padang modified. Thismodification does not pay attention to the safety of public transportation and passenger comfort.The problems studied are Motif-route public transportation driver Modifying Siteba - Pasar RayaPadang. The purpose of this study was to describe the motive of public transportation driver ModifyRoute Siteba-Pasar Raya Padang.The theory used in this study is a phenomenological theory of Alfred Scuhtz with theconcept in order motive ( goal ) and Because motive ( of the past ). This study is a qualitative studyusing deskriktif approach. The technique of taking informants done by intentionally (purposivesampling) the number of informants 9 people. The method of collecting the data used in this studyis the non-participant observation and in-depth interviews with structured types. Sources of data inthis study, there are two primary data and secondary data. Primary data were obtained directlyduring interviews and secondary data obtained from the relevant authorities in this research that thetransportation department and FORKAS (Siteba transport communication forum). Location ofresearch in this study is Padang precisely track public transportation route Siteba Kingdom Market .While the data analysis techniques used in this study Milles and Huberman analysis.The results of this study revealed that the motive for the driver to modify the publictransportation can be grouped into five categories, among others: a ) as an attention getterpassengers, b ) as a way of self-indulgence, c ) as channeling the soul of art, d ) as a way to increaserevenue, and e ) as a way get a reward. The research results are concentrated in the order of motivein this study was modified as a way attract the attention of passengers, art, self-satisfaction,increased revenue and reward. While the lack of interest in Because motive is the publictransportation of passengers when not modified.